Community Service Report: Islamic Education Teachers' Work Program in Realizing SDGs 4 - Muhammad Numan; Youcha Alassane Toure (Islamic Studies and Development Center (ISDC) Universitas Negeri Padang, 2025)
Islamic education teachers have significant duties and responsibilities in society. As outstanding individuals, teachers educate students in formal and non-formal schools. Furthermore, as members of society, teachers must be role models and examples as mentors in the community in realizing the ideals and goals of mutual progress (SDGs4). This study aims to find out what Islamic education teachers do as a form of real work in the community. This study uses a qualitative method with an ethnographic approach. Data sources were obtained from fifteen informants through in-depth interviews selected using purposive sampling techniques. To strengthen the interview data, the author also conducted observations by directly participating in various real activities of the teachers who were the subjects of the study. All data were analyzed using Miles and Huberman's thematic technique. The research findings show five activities carried out by Islamic education teachers in realizing ideals and mutual progress in the community. The five activities are: i) establishing learning communities for all segments of society, ii) actively participating in the management and development of houses of worship, iii) establishing literacy centers, iv) implementing environmental conservation programs, and v) collaborating to realize inclusive education. These five findings can serve as examples for Islamic education teachers in carrying out community-based work within society to achieve SDGs 4.